Quorum sensing : understanding the role of bacteria in meat spoilage - Blana, Vasiliki A (Cranfield University, 2010)
Quorum sensing is a fundamental process to all of microbiology since it is ubiquitous in the bacterial world, where bacterial cells communicate with each other using low molecular weight signal molecules called autoinducers. Despite the fact that quorum sensing regulates numerous bacterial behaviours, very few studies have addressed the role of this phenomenon in foods. The microbial association of beef consists mainly of pseudomonads, Enterobacteriaceae, Brochothrix thermosphacta and lactic acid bacteria as revealed by minced beef samples purchased from retail shops, which fluctuates according to the storage conditions. Certain members of the microbial association, which are considered to produce signal molecules, have been found to be major contributors to meat spoilage. Pseudomonas fragi and Enterobacteriaceae strains, i.e., Hafnia alvei and Serratia liquefaciens are among the most common quorum sensing signal producers recovered from various food environments. Cont/d.